Performance of quadrature amplitude modulation orthogonal frequency division multiplexing‐based free space optical links with non‐linear clipping effect over gamma–gamma modelled turbulence channels. Issue 5 (1st October 2015) - Nistazakis, Hector E.; Stassinakis, A.N.; Sinanović, Sinan; Popoola, Wasiu O.; Tombras, George S.
Abstract : The free space optical (FSO) communication systems have attracted significant research and commercial interest in the last few years because of their low installation and operational cost along with their very high performance characteristics. However, for terrestrial FSO links, the optical signal propagates through the atmosphere which exhibits time‐varying behaviour that implies variations in the links' performance. In this study, the authors estimate the performance metrics for terrestrial FSO links which are using the orthogonal frequency division multiplexing (OFDM) technique with a quadrature amplitude modulation scheme over turbulence channels. More specifically, the authors investigate the influence of the non‐linear clipping effect of the OFDM scheme, along with the atmospheric turbulence modelled using the gamma–gamma distribution. Both effects significantly influence the performance of the link and here the authors derive closed form mathematical expressions for the estimation of the average signal to noise ratio, the outage probability and the average bit error rate that are vital for FSO system performance characterisation. Finally, using these expressions, the authors present the corresponding numerical results for common parameter values of the FSO links and investigate the accuracy of the expressions for marginal cases with nearly negligible turbulence effect.